ANALISIS YURIDIS LARANGAN PEMBAYARAN HONORARIUM KEPADA PEMBINA YAYASAN DALAM UNDANG-UNDANG NOMOR 28 TAHUN 2004 TENTANG YAYASAN (STUDI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 5/PUU-XIII/2015) - JESIE SALIM (PREMISE LAW JURNAL, 2017)
As a legal entity consisting of the assets that are separated and intended to achieve social, religious and humanitarian purposes, foundation is prohibited to transfer its assets to its bodies. The prohibition, accompanied by criminal sanctions to those who violate it, induced a protest from a foundation manager, Dahlan Pido, who files a request to examine the regulation, leading to Constitutional Court’s Ruling No. 5/PUU-XIII/2015. The research showed that the management of the foundation’s duties and functions are limited as far as the Articles of Association and Law on Foundation allow. Prohibition on fee payment is to ensure that foundation’s assets are used only to reach foundation’s purposes. The research also found that the consideration of the Constitutional Court’s Panel of Judges to deny the request of Dahlan Pido was accurate and in accordance with legal provisions as well as Rights without Subject Theory, Social Purposes Theory and Utility Theory. Keywords: Foundation, Management of Foundation, Payment, Fee